The effect of temperature on the physiological condition and growth performance of freshwater eel elver Anguilla bicolor bicolor McClelland, 1844 - Fekri, Latifa; Affandi, Ridwan; Rahardjo, Muhammad Fajar; Budiardi, Tatag; Simanjuntak, Charles Parningotan Haratua; Fauzan, Tezza; Indrayani, Indrayani (Indonesian Society of Scientific Aquaculture (ISSA), 2018)
ABSTRACT This study aimed to analyze the effect of water temperature on the physiological condition and growth performance of freshwater eel elver Anguilla bicolor bicolor (McClelland, 1844). This study was conducted in March 2017 at the Physiology Laboratory of Aquatic Animal, Faculty of Fisheries and Marine Sciences, Bogor Agricultural University. The study used a completely randomized design with five different levels of temperature (22°C, 24°C, 26°C, 28°C, and 30°C) as treatments with two replications. The size of elver was 2‒3 g. Fish were fed with 1 mm pellet containing 45% of protein. The feeding level was 7 % of fish biomass and the feeding frequency was two times a day. The results showed that temperatures range from 24‒30°C could be used for freshwater eel elver rearing and 28‒30°Cwere the best temperatures to support survival and growth performance of eel elver. A temperature of 24°C was the best temperature that could reduce the metabolism rate and did not cause stress on the elver. Keywords: elver, physiological conditions, growth performance, metabolism, temperature ABSTRAK Penelitian dengan tujuan menganalisis pengaruh suhu terhadap kondisi fisiologis dan kinerja pertumbuhan elver ikan sidat (Anguilla bicolor bicolor McClelland, 1844) telah dilakukan pada bulan Maret 2017 di Laboratorium Fisiologi Hewan Air FPIK IPB. Penelitian menggunakan rancangan acak lengkap dengan lima perlakuan suhu berbeda (22°C, 24°C, 26°C, 28°C, dan 30°C) dengan masing-masing dua ulangan. Ukuran benih yang digunakan 2‒3 g. Pakan yang diberikan berupa pellet berukuran 1 mm dengan kadar protein 45%. Jumlah pakan yang diberikan (FR) adalah 7% dari biomassa ikan dan diberikan dua kali sehari. Hasil penelitian menunjukkan bahwa kisaran suhu 24‒30°C dapat digunakan dalam pemeliharaan elver ikan sidat, dan suhu 28‒30°C merupakan suhu yang sangat baik untuk mendukung kelangsungan hidup dan pertumbuhan elver ikan sidat. Suhu media 24°C adalah suhu terbaik yang dapat menekan laju metabolisme dengan tidak menyebabkan stres pada elver ikan sidat. Kata kunci: elver, kondisi fisiologis, kinerja pertumbuhan, metabolisme, suhu